Serum Adropin Levels Are Elevated in Patients With Hyperthyroidism - Xin Wang; Xiaona Chang; Qiu Wang; Xiaoyu Ding; Jiaxuan Wang; Ruixiang Cui; Guang Wang; Jia Liu (International Journal of Endocrinology)
Conclusions: Patients with hyperthyroidism had elevated serum adropin levels. And the serum adropin concentrations were independently correlated with the FT3 and TSH levels.